Attracting Foreign Direct Investment into Tunisia through Outreach Campaigns - Sabha, Yassin; Hamden, Mouna; Heilbron, Armando (World Bank, Washington, DC, 2020)
After the Arab Spring, Tunisia urgently needed to create productive jobs and economic opportunities for its young population. Attracting foreign direct investment (FDI) in priority sectors was a key pillar of the Government’s strategy to deliver this job agenda. With the support of the World Bank Group, the Investment Promotion Agency of Tunisia engaged in proactive outreach campaigns which resulted in 21 investment leads and three announced FDI projects, including a manufacturing plant by Japan’s Sumitomo. This case study shows that well-planned and executed investor outreach campaigns can lead to concrete investment results and contribute to a country’s development objectives. It provides key success factors useful to other countries wanting to engage in outreach. More than ever before (in a post-COVID-19 world), outreach can play a key role for countries in their efforts to reposition and take advantage of new investment opportunities from near shoring and emerging sectors. The paper provides examples of IPAs continuing their outreach efforts virtually by leveraging technology.